If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = -3x + 4x + 4 Reorder the terms: 6 = 4 + -3x + 4x Combine like terms: -3x + 4x = 1x 6 = 4 + 1x Solving 6 = 4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + -1x = 4 + 1x + -1x Combine like terms: 1x + -1x = 0 6 + -1x = 4 + 0 6 + -1x = 4 Add '-6' to each side of the equation. 6 + -6 + -1x = 4 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 4 + -6 -1x = 4 + -6 Combine like terms: 4 + -6 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| -49=-7/9y | | 4v/3=-16 | | -7/5u=35 | | 4(a+2)+3(a+3)=10 | | 5-4(2x+6)=5(2-x)-3x | | Tbc=0 | | y^2+y=1 | | 6/1/3/8 | | 40*.8= | | 1/6x3= | | x+x+6+3x=36 | | 9/x=-6 | | (3/2x)-(2/3)=(7/4)-(1/3x) | | 4v-7=9(v-3) | | -2(u-5)=-4u+8 | | -8y-6=9(y+5) | | 8(x+8)-2x=22 | | 3(v-6)+6v=-36 | | 30=6(w+3)-4w | | 7-6y=33 | | 20-6y=33 | | 10a-7=73 | | 10a-7=72 | | 10a-7=78 | | 10a-2=48 | | 5x+7x-2x= | | 3(3d-5)=2(d+8) | | 5x-4-4x-13=20 | | 3x+4=3x+10 | | t+14=34-37 | | -6(x-9)=-8x+44 | | x/((0.005-x)(2-4x)^4) |